Determination of the Critical Phases of the Experimental Research Using Laboratory Animals: Risk Analysis - S. V. Khodko; M. N. Makarova; V. G. Makarov; S. S. Salynov; N. V. Rodionova (Регуляторные исследования и экспертиза лекарственных средств)
Critical phases (stages) of preclinical studies are those procedures or types of research activities whose accurate and correct implementation is a prerequisite for obtaining valid and reliable results. Russian and foreign standards require determination of the critical phases of each individual study by quality assurance staff based on checking the study protocol (plan).The aim of the study was to identify critical phases typical for most preclinical studies, and assess the potential risks during inspections.Materials and methods: the study was carried out by analysing the types and consequences of nonconformities. Numerical parameters of risks were analysed for each critical phase of the preclinical study identified by quality officers of the Joint Stock Company “Scientific and Production Association ‘HOME OF PHARMACY’”.Results: it was discovered that incorrect implementation of a procedure constituted a potential nonconformity at all the identified critical phases, and a potential consequence was acquisition of low-quality data. A combination of incorrectly implemented procedures at two or more critical phases could pose an unacceptable risk and lead to complete loss of data or failure to process data, and, as a result, the need to repeat the study.Conclusions: the highest risk was identified for such critical phases as preparation and administration of final doses of test samples, performance of physiological tests, collection of biological material samples, and handling of biological material samples by other relevant departments. Summarising the data obtained on the risks of all the critical phases, it can be concluded that risk action should take the form of regular inspections by the quality assurance staff and the study director. By adjusting the frequency of inspections, the risk of each critical phase can be made insignificant.